2012
DOI: 10.1093/jac/dks178
|View full text |Cite
|
Sign up to set email alerts
|

The role of eis mutations in the development of kanamycin resistance in Mycobacterium tuberculosis isolates from the Moscow region

Abstract: Our study shows that the eis promoter region is a useful molecular marker of kanamycin resistance in the Moscow region. Complex analysis of rrs and eis mutations will significantly reduce the time to diagnose kanamycin resistance in TB patients, compared with phenotypic drug resistance testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
36
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 4 publications
5
36
2
Order By: Relevance
“…The other four specimens were KAN s in both DST runs, indicating that these mutants had MICs below the tested KAN critical concentration. While eis promoter mutations have been well documented to confer only low-level KAN resistance (21,44), recent studies have found M. tuberculosis eis mutants to have broad KAN MIC ranges (0.625 to 32 g/ml) via liquid-based DST methods (45,46). As such, the eis promoter mutants identified in our study may have had MICs around the critical concentration.…”
Section: Rifmentioning
confidence: 63%
“…The other four specimens were KAN s in both DST runs, indicating that these mutants had MICs below the tested KAN critical concentration. While eis promoter mutations have been well documented to confer only low-level KAN resistance (21,44), recent studies have found M. tuberculosis eis mutants to have broad KAN MIC ranges (0.625 to 32 g/ml) via liquid-based DST methods (45,46). As such, the eis promoter mutants identified in our study may have had MICs around the critical concentration.…”
Section: Rifmentioning
confidence: 63%
“…In recent studies conducted on clinical strains isolated in Estonia, Vietnam, and South Africa, the sensitivity of the assay for the detection of resistance to KAN was very low (reaching 43% at its maximum) (16,22,23), probably due to the high prevalence of Beijing strains harboring mutations in eis genes not recognized by the assay and responsible for conferring resistance to KAN only, as was shown in Vietnam (23). Absence of cross-resistance to AMK and CAP in strains harboring mutations in the eis promoter region has been recently demonstrated in a genomic study of resistance in Samara, Russia (24), and in another study conducted in Russia (25). In a previous large study conducted in Samara, a significant proportion of Beijing KAN-resistant and AMK-sensitive strains was found to contain mutations in the eis gene but not in the rrs gene (24).…”
Section: Discussionmentioning
confidence: 86%
“…More needs to be understood about the relationships of these mutations and their CAP-specific MICs to improve the clinically relevant predictive value of molecular diagnostics for detecting phenotypic CAP r . Like the INH r that is caused by both katG and inhA promoter mutations, phenotypic KAN r is caused by mutations in both rrs and the eis promoter (40,41). Due to regional variations in the frequencies of eis and rrs mutations in the KAN r isolates that we observed, we predict that rapid diagnostic methods, such as the Hain Lifescience MTBDRsl, which detect only rrs SNPs and not eis promoter SNPs, will underestimate KAN r significantly in countries like Moldova (which had mostly eis mutations in KAN r isolates).…”
Section: Discussionmentioning
confidence: 99%